Sustainable Entrepreneurship : Corporate Entrepreneurship yang Berkelanjutan pada PT Industri Jamu dan Farmasi Sido Muncul Tbk - Achmada, Aurora Yupita; Purbasari, Ratih; Purnomo, Margo (Jurnal Bisnis dan Kewirausahaan, 2025)
The purpose of this study is to analyze how PT Industri Jamu dan Farmasi Sido Muncul Tbk implements sustainable entrepreneurship (SE) by using the triple bottom line (TBL) approach, find challenges to implementing it, and evaluate how it impacts the sustainability and performance of the company. The qualitative research used content analysis and descriptive analysis. Secondary data sources used were annual reports, sustainability reports, and scientific articles. The results of the analysis show that Sido Muncul successfully reduced greenhouse gas emissions by 80.3% and achieved renewable energy use of 88%. In addition, the company increased employee training hours by 5.4% and improved community collaboration. The company focused on product innovation and operational efficiency in order to maximize profit, despite revenue fluctuations. Climate change, strict regulations, and limitations in internal and external sustainability management are the main obstacles. This study helps improve our knowledge of how sustainable entrepreneurship (SE) fits into corporate entrepreneurship (CE), especially in the traditional herbal medicine industry in developing countries that depend on local knowledge.